Leveraging the Crisis for Equity and Access in the Long Term: A Brief Research Report - Virella, Patricia Marisol; Cobb, Casey (Frontiers in Education, 2021)
For years, crises have occurred in and out of schools. For years, crises have occurred in and out of schools. School leaders have had to make meaning of these crises and lead through them. Popular rhetoric in today’s media describes the educational inequities children have faced as a result of the current crisis, the COVID-19 pandemic. In an effort to understand how school leaders respond to the COVID-19 pandemic, we spoke directly to principals, listening for ways in which they confronted issues of inequity. Our research was guided by the question: how do principals engage in equity activities while leading through the COVID-19 crisis? This study focuses on the opportunity’s principals have created during the COVID-19 pandemic to address issues of equity in their schools. We present three main findings resulting from our data analysis. Overall, our findings indicate principals acted upon two primary opportunities for achieving equity in their school community. The findings from our study illustrate two specific opportunities principals were presented with as a result of the crisis to engage in equity responses.